EXPLORING DNA ISOLATION TECHNIQUE: A GUIDE FOR EDUCATORS AND STUDENTS - Siti Masruroh; Wati, Dwi Retno (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study is intended to guide educators or students who will conduct DNA isolation experiments to prove and view the presence of DNA contained in fruit using a simple method. DNA isolation is a method to obtain or research deoxyribonucleic acid from an organism. The basic principle in DNA isolation is to break or extract a tissue so that a cell extract contains DNA, RNA, and other essential substances will be formed. DNA isolation experiment is intended to determine a simple method of isolating DNA in fruit and to determine the effectiveness of detergents used for DNA isolation. In this experiment, to observe DNA, DNA isolation was carried out on the crushed fruits to form juice from the fruit. Then, make a solution from a mixture of detergent and water. Later, mix the fruit juice with a detergent solution and add salt to it. Once the solution is homogeneous, filter it and add cold ethanol. Then, the DNA strands will appear because of the reaction. The results obtained are influenced by the type of detergent used, the type of fruit used, the alcohol concentration, and the results of the filtering performed.